1999
DOI: 10.1002/(sici)1521-3757(19990115)111:1/2<147::aid-ange147>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

[1,3]-, [3,3]- und [3,5]-sigmatrope Umlagerungen von Estern sind pseudopericyclisch

Abstract: Symmetrieerlaubt ist die [3,5]‐sigmatrope Umlagerung des Esters 1. Die Barriere dieser Umlagerung ist nach Ab‐initio‐Rechnungen bemerkenswerterweise sogar niedriger als die der konkurrierenden [3,3]‐Umlagerung. Dieses überraschende Ergebnis ist die Folge einer ausbleibenden Orbitalüberlappung im pseudopericyclischen Übergangszustand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The [3,5]-sigmatropic shift of a dienyl ester predicted to follow a pseudo-pericyclic mechanism. [15] transition structure. Both B3LYP and BPW91 predict that hS 2 i 1.03 for the diradical intermediate, which indicates that the diradical is nearly 50:50 singlet and triplet, and the singlet and triplet are nearly degenerate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [3,5]-sigmatropic shift of a dienyl ester predicted to follow a pseudo-pericyclic mechanism. [15] transition structure. Both B3LYP and BPW91 predict that hS 2 i 1.03 for the diradical intermediate, which indicates that the diradical is nearly 50:50 singlet and triplet, and the singlet and triplet are nearly degenerate.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Birney et al have found that formal [3,5]-sigmatropic shifts of several dienyl esters (Scheme 5) are actually pseudopericyclic processes, not involving a cyclic delocalized system and not subject to the Woodward ± Hoffmann rules. [15] Such processes are facilitated by the involvement of lone pairs in orbitals orthogonal to the p-system. These lone pairs are absent in the all-hydrocarbon process, and a pseudopericyclic process is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…First, these transition structures are neither aromatic nor antiaromatic, because they lack a loop or interacting orbitals. This means that no pseudopericyclic reaction can be forbidden, but they are always orbital symmetry allowed. ,, Second, because these reactions can avoid the electron−electron repulsion inherent in a cyclic overlap of orbitals, they can often have very low or even nonexistent barriers in situations where the geometry, nucleophilicity, and exothermicity are favorable. ,,
…”
Section: Introductionmentioning
confidence: 99%